CANTIK, SEKSI, DAN ENERJIK: PENGGUNAAN PRODUK-PRODUK KIMIA DI KALANGAN SEXY DANCER DI YOGYAKARTA - , CAROLINA RETMAWATI PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job as sexy dancer that use their body to work to earn money make them need to treat their body. They always trying to give their best performance to become professional sexy dancer. Many efforts done by sexy dancer to have perfect body. A way related with performance in their body are by using chemical products that sexy dancer believe can improve their performance when doing their job. Baudrillard (2004:168-169) said if body that harmonized are directly inside objective capitalist function in other words if body been seeing as capital, this mean they can make profit from their body. What Baudrillard said if related to job as a sexy dancer we can see that body used by sexy dancers to earn money to their pocket. Those condition make them doing many efforts to improve appeal from inside their body. One way that used is using or consuming chemical products. From that question appear what are chemicals products that used by the sexy dancer to improve their performance? The research conducted at Yogyakarta starts from May to December 2013. Yogyakarta itself well known as the city of students and tourism. This research did with interview (in-depth interview) to collecting data and head to toe (HTT) strategy to 10 informants that recruited with snowball sampling. They consist of 5 sexy dancer regular and 5 sexy dancer long trip. Collecting ten informants are not easy because writer have to adjust with informantâs activity. The research show that to keep good appearance needs many chemical products either to support their job or overcome risk from their job. Hair, skin and body, stamina, and miss V become important part of the body that sexy dancer really concern about it. Those parts get more attention so in one part can be found that many products that used together in that part but sometimes it also can disturb their health. Many chemical products that use adjusted with the condition of the job and economic condition from the sexy dancer.